Representasi Pemaknaan Pesan Pada Lirik Lagu Yet To Come Karya Bangtan Sonyeondan (BTS) Bagi Army Palembang - Nasution, Nurseri Hasnah; Sifa, Suci Widyastiani Puteri; Walian, Anang (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
Music is one medium that can be used to convey messages. In music, of course, there are lyrics made by the songwriter regarding a message to be conveyed to listeners and each song has its own meaning for those who listen. Likewise what BTS (Bangtan Sonyeondan) wants to convey through one of their songs from the proof album entitled Yet To Come. This research includes a descriptive qualitative method using Roland Barthes' semiotic analysis. Barthes's thinking includes denotation, connotation, and myth. Using primary and secondary data as the data source used, while the data collection technique was carried out in a triangulation (combined) manner consisting of observation, literature study, and interviews. From the results of this study, it was found that the meaning of messages about dreams, hopes, and motivations told by BTS through their career journeys were then poured into the lyrics of the song Yet To Come. For ARMY in Palembang City, this song has a positive message with a deep meaning because it can motivate young people, including ARMY, not to give up and rise from their difficult times.